2021
DOI: 10.1097/md.0000000000026705
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of Tocilizumab and steroid for management of COVID-19 associated cytokine release syndrome

Abstract: Cytokine release syndrome (CRS) or cytokine storm is thought to be the cause of inflammatory lung damage, worsening pneumonia and death in patients with COVID-19. Steroids (Methylprednislone or Dexamethasone) and Tocilizumab (TCZ), an interleukin-6 receptor antagonist, are approved for treatment of CRS in India. The aim of this study was to evaluate the efficacy and safety of combination therapy of TCZ and steroid in COVID-19 associated CRS.This retrospective cohort study was conducted at Noble hospital and Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
(155 reference statements)
0
6
0
Order By: Relevance
“… 10 Despite the lack of consensus on treating COVID-19 patients; the commonly used medication is interleukin-6 (IL-6) receptor antagonist (tocilizumab). 22 In our case series, two (Cases I and II) out of the seven patients were treated with tocilizumab (TCZ), with one patient (Case II) having a favorable outcome. In a retrospective cohort study, 515 patients received TCZ and steroids, with an estimated 73.8% having clinical improvement.…”
Section: Discussionmentioning
confidence: 93%
“… 10 Despite the lack of consensus on treating COVID-19 patients; the commonly used medication is interleukin-6 (IL-6) receptor antagonist (tocilizumab). 22 In our case series, two (Cases I and II) out of the seven patients were treated with tocilizumab (TCZ), with one patient (Case II) having a favorable outcome. In a retrospective cohort study, 515 patients received TCZ and steroids, with an estimated 73.8% having clinical improvement.…”
Section: Discussionmentioning
confidence: 93%
“…Antifibrotic therapies against fibrosis due to COVID-19 were also reported. Antifibrotic agents involving pirfenidone and nintedanib ( 43 , 44 ), immune inhibitors ( 45 ), mesenchymal stem cell (MSC) therapy ( 46 , 47 ), lung transplantation ( 27 , 48 ), prolonged oxygen support, and rehabilitation exercise ( 49 ) might exert beneficial effects in preventing pulmonary fibrosis following COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this study, tocilizumab was reported to increase the incidence of VAP in critical COVID-19 patients ( Ceccarelli et al, 2021 ). In addition, it is reported that combination therapy of tocilizumab and steroids is likely to be conducive to managing COVID-19-associated cytokine release syndrome ( Dravid et al, 2021 ). While another research suggested that adding tocilizumab to methylprednisolone did not improve outcomes significantly ( Hamed et al, 2021 ).…”
Section: Drug Treatment Of Ventilator-associated Pneumonia In Covid-1...mentioning
confidence: 99%